(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2022)
Background: Paediatric migraine is the most common cause of recurrent headache in children. Objective: The purpose of the study was to assess the efficacy and tolerability of topiramate for prophylactic treatment of children suffering from moderate migraine. Methodology: This randomized controlled trial was done in the outpatient department of Paediatric Neurology at National Institute of Neurosciences, Dhaka, Bangladesh from January to July, 2018. Children of 5 to 15years with migraine of moderate intensity were randomized into study group (TPM treatment group) and control group (FNZ treatment group). The efficacy and safety of TPM was assessed after 4 months of treatment. Results: There was significant reduction of frequency of headache /month in both groups after treatment (within group, 4.65 ± 1.59 vs1.70 ± 0.73, p <0.001 for FNZ, 5.20 ± 1.73 vs 1.75 ± 0.71, p <0.001 for TPM). The efficacy of two drugs was not different in moderate intensity of migraine p being 0.304 and 0.828. Conclusion: Topiramate is effective as well as safe in prophylaxis of children suffering from moderate migraine. Journal of National Institute of Neurosciences Bangladesh, January 2022; 8(1):19-22